Effect of adhesive replacement with cement mortar on NSM strengthened RC Beam - Moshiur Rahman, Md.; Zamin Jumat, Mohd; Akter Hosen, Md.; Saiful Islam, A. B. M. (Revista de la Construcción. Journal of Construction, 2016)
This paper presents the experimental behavior of reinforcement concrete beams strengthened with near surface mounted (NSM) steel bar. Several researchers have used NSM fiber reinforced polymer (FPR) bar or strip for strengthening reinforced concrete beams. Though FRP has a number advantages like high strength, light weight and corrosion resistance it doesn’t show any ductile behavior, still highly expensive and not easily available in market. On the other hand, steel bar is less expensive, readily available in the market and shows good ductility. In order to get rapid and economic strengthening solution, strengthening with near surface mounted steel bar may become a potential alternative to retrofit reinforced concrete members. Therefore, the main purpose of this paper to investigate the experimental behavior of reinforced concrete beam strengthened with near surface mounted steel bar. Seven full-size beams (one control beams and six strengthened beams) were tested. Steel bars were used for strengthening. The failure load, mode of failure, deflection, and strain behavior are discussed. The study reveals that the near surface mounted technique with steel bars and cement mortar is the most economical strengthening solution to increase the flexural performance of RC beams.